Derivative Instrument and Earnings Management: Does Listing on the Stock Exchange matter? - Valdiansyah, Riyan Harbi; Murwaningsari, Etty; Mayangsari, Sekar (IJOSMAS, 2022)
The researcher conducted this study to obtain empirical evidence of derivative instruments, on the earnings management, which was moderated by listing factors on the Indonesian Stock Exchange in banking industry for the 2015-2020 period. This study applies a quantitative approach, which highlights the analysis of numerical data processed by statistical procedures. This study applies unbalanced panel data with 268 banking data listed and non-listed on the Indonesia Stock Exchange. The results describe that derivative instrument negatively effect on earnings management, while the listing factor has a positive impact on earnings management. In addition, banks listed on the Indonesia Stock Exchange have a lower effect of derivative instruments on earnings management. This study has limitations in terms of the use of variables that have not considered the effect of implementing IFRS 9 on the provision of defaulted loans which may have different results if this is considered. In the end, the researcher hopes that the authorities will increase the effectiveness of monetary policy transmission by increasing derivative transactions with hedging purposes that can function as a tool to minimize bank profits. In addition, further research can use other variables that affect banking earnings management by adding new indicators to make this measurement robust and generally accepted.